FOREIGN TOURIST COMFORT IN AN ISLAMIC SHARIA GOVERNED DESTINATION: A MIXED-METHOD STUDY IN SABANG, ACEH, INDONESIA - Eka Octavian Pranata; Nabila Fadhilah; Cut Dian Fitri; Rahmatul Zhiqrie (El-Mubarak: Islamic Studies Journal, 2026)
This study investigates the comfort level of foreign tourists visiting Sabang, Aceh, Indonesia, within the framework of Islamic Sharia law enforcement. As a Special Autonomy Region, Aceh implements Sharia-based regulations that significantly shape the tourism experience, including dress codes, behavioral norms, and halal requirements. Using a mixed-method approach combining survey questionnaires (n = 187 foreign tourists) and in-depth interviews (n = 15 participants), data were collected at key tourist sites in Sabang during 2024. The Tourist Comfort Index (TCI) and thematic analysis were employed for quantitative and qualitative data, respectively. Results indicate that the majority of foreign tourists (71.1%) reported moderate to high comfort levels, primarily attributing positive experiences to the natural beauty, local hospitality, and cultural uniqueness of the destination. However, challenges were noted regarding the enforcement of dress codes and limited nightlife options. Regression analysis reveals that prior knowledge of Sharia regulations (β = 0.42, p < 0.001), respectful interaction with locals (β = 0.38, p < 0.001), and availability of tourism information in multiple languages (β = 0.29, p < 0.01) are significant predictors of tourist comfort. The findings contribute to the emerging discourse on halal tourism, destination marketing, and intercultural respect in religiously conservative destinations.